Exploring Fish Varieties and Biofloc Technology - Ranibai, Ranibai; Swat, Swat; Gayatri, Gayatri (Journal of Neonatal Surgery, 2025)
Aquaculture is a fast-growing industry that requires efficient resources and space utilization. Various technologies have been developed to overcome challenges, with "Biofloc systems" being a recent innovation aiming to address water pollution, optimize water usage, and recycle nutrients through bacteria communities. By adopting this system, aquaculture farms can reduce or eliminate water exchange, while also benefiting from microbial by-products. Fish experience quicker response times due to elevated water respiration rates but may face seasonal performance issues in sunlight-exposed systems. Alkalinity supplements may be necessary, along with increased energy requirements for mixing and aeration, a startup period, and potential pollution risks from nitrate accumulation and notification instability.